MEDIASI DAN ARBITRASE UNTUK MENCARI KEADILAN BERSAMA - Yudhi Widyo Armono,; Antarez Endy Yafentra, (Journal of Innovation Research and Knowledge, 2024)
The collective agreement that results from Mediation is the same as the legal content with the Court's decision. Although the Mediation method is far more efficient, the public's interest in resolving disputes through Mediation is far less than the Court. The public arguing their case with the Court is to look for a court decision that satisfies him, not the mediation orientation sought. It is difficult to change in the short term about the ethos of culture in society, because people seem satisfied when they can see the defeated parties suffer. Changing the mindset of society from punishing and suffering to deliberation for the common good. Continuous socialization was held regarding the importance of mediation to resolve disputes